2015
DOI: 10.1007/s00784-015-1583-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pH and fluoride concentration of dentifrices on fluoride levels in saliva, biofilm, and biofilm fluid in vivo

Abstract: Toothbrushing with acidic toothpastes leads to slight increases in F concentrations in the biofilm fluid when compared to neutral formulations, which may contribute to the higher anticaries effect of acidic formulations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 31 publications
2
6
1
1
Order By: Relevance
“…A higher concentration of fluoride in saliva was observed one hour after application of the fluoridated products. Studies have observed higher concentration of fluoride one hour after the application of dentifrices [18] and fluoridated varnishes [15], as observed in the present investigation. In addition, another study observed greater fluoride release one hour after the application of Duofluorid ® varnishes and experimental varnish containing 5% of CaGP (calcium glycerophosphate).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…A higher concentration of fluoride in saliva was observed one hour after application of the fluoridated products. Studies have observed higher concentration of fluoride one hour after the application of dentifrices [18] and fluoridated varnishes [15], as observed in the present investigation. In addition, another study observed greater fluoride release one hour after the application of Duofluorid ® varnishes and experimental varnish containing 5% of CaGP (calcium glycerophosphate).…”
Section: Discussionsupporting
confidence: 87%
“…The higher fluoride release observed in the AG group can be explained by the increase in the reactivity of calcium and fluoride to form CaF2 reservoirs due to the acid present [5,30]. One study observed higher fluoride concentration after application in biofilms treated with acid dentifrices than with their neutral counterparts [18]. This aspect, however, has not been proven in this investigation.…”
Section: Discussioncontrasting
confidence: 53%
“…In this sense, it should be noted that the addition of polyphosphates is only one of the possibilities to increase the anticaries effect of LFDs. Promising results have been reported for LFDs at acidic pH, which have been shown to increase the reactivity with tooth enamel [20], besides increasing fluoride concentrations in enamel [35], biofilm [32] and in the biofilm fluid [36] in comparison with a neutral 1100 ppm F formulation. Acidic LFDs have been tested in two randomized controlled clinical trials, which was shown to have a similar effect on caries progression when compared to 1100F dentifrices , at the same time as it significantly reduced fluoride intake and its subsequent absorption and accumulation in fingernails [32].…”
Section: Discussionmentioning
confidence: 99%
“…This result is consistent with previous data showing higher F concentrations in whole biofilm samples 1 h after brushing with F dentifrices, which returned to baseline (placebo) values 12 h after the use of a conventional toothpaste [24]. Also, fluoride concentrations in saliva and dental biofilm collected 8 h after the last use of fluoride products (dentifrices and fluoride solution) did not differ among treatments (placebo, 1100 ppm F, and 1100 ppm F + fluoride solution), suggesting that F products for home-use have no long-term effect on fluoride concentrations in saliva and in dental biofilm, mainly in residents of an area with a fluoridated water supply [25,26].…”
Section: Discussionmentioning
confidence: 99%